The stigma of mental health problems and other barriers to care in the UK Armed Forces - Thornicroft Graham; Rona Roberto J; Hotopf Matthew; Greenberg Neil; Hughes Jamie; van Staden Lauren; Iversen Amy C; Wessely Simon; Fear Nicola T (BMC, 2011)
Abstract Background As with the general population, a proportion of military personnel with mental health problems do not seek help. As the military is a profession at high risk of occupational psychiatric injury, understanding barriers to help-seeking is a priority. Method Participants were drawn from a large UK military health study. Participants undertook a telephone interview including the Patient Health Questionnaire (PHQ); a short measure of PTSD (Primary Care PTSD, PC-PTSD); a series of questions about service utilisation; and barriers to care. The response rate was 76% (821 participants). Results The most common barriers to care reported are those relating to the anticipated public stigma associated with consulting for a mental health problem. In addition, participants reported barriers in the practicalities of consulting such as scheduling an appointment and having time off for treatment. Barriers to care did not appear to be diminished after people leave the Armed Forces. Veterans report additional barriers to care of not knowing where to find help and a concern that their employer would blame them for their problems. Those with mental health problems, such as PTSD, report significantly more barriers to care than those who do not have a diagnosis of a mental disorder. Conclusions Despite recent efforts to de-stigmatise mental disorders in the military, anticipated stigma and practical barriers to consulting stand in the way of access to care for some Service personnel. Further interventions to reduce stigma and ensuring that Service personnel have access to high quality confidential assessment and treatment remain priorities for the UK Armed Forces.